Effectiveness and safety of brucea javanica oil assisted TACE versus TACE in the treatment of liver cancer: a systematic review and meta-analysis of randomized controlled trials - Wu, Zhi-Hai; Zhang, Hai-Feng; Li, Jun-Yan; Diao, Yi-Rui; Huang, Man-Jing; Gao, Dong-Yang; Liang, Chang-Hao; Luo, Zhi-Qiang (Frontiers in Pharmacology, 2024)
The effectiveness and safety of using Brucea javanica oil (BJO) in combination with Transarterial Chemoembolization (TACE) for liver cancer treatment are subjects of debate. This study aims to assess the comparative effectiveness and safety of BJO-assisted TACE versus TACE alone and quantifies the differences between these two treatment methods.Methods: A systematic search was conducted in multiple databases including PubMed, Cochrane, CNKI, and Wanfang, until July 1, 2023. Meta-analysis was conducted, and the results were presented as mean difference (MD), risk ratio (RR), and 95% confidence intervals (CI).: The search yielded 11 RCTs, with a combined sample size of 1054 patients. Meta-analysis revealed that BJO-assisted TACE exhibited superior outcomes compared to standalone TACE. Specific data revealed that BJO-assisted TACE improves clinical benefit rate by 22% [RR = 1.22, 95% CI (1.15, 1.30)], increases the number of people with improved quality of life by 32%, resulting in an average score improvement of 9.53 points [RR = 1.32, 95% CI (1.22, 1.43); MD = 9.53, 95% CI (6.95, 12.10)]. Furthermore, AFP improvement rate improved significantly by approximately 134% [RR = 2.34, 95% CI (1.58, 3.46)], accompanied by notable improvements in liver function indicators, with an average reduction of 27.19 U/L in AST [MD = -27.19, 95%CI (-40.36, -14.02)], 20.77 U/L in ALT [MD = -20.77, 95% CI (-39.46, -2.08)], 12.17 μmol/L in TBIL [MD = -12.17, 95% CI (-19.38, -4.97)], and a decrease of 43.72 pg/ml 5 in VEGF ]. Most importantly, there was a 29% reduction in the occurrence of adverse reactions [RR = 0.71, 95% CI (0.60, 0.84)].These findings indicate that BJO-assisted TACE may be considered as a potentially beneficial treatment option for liver cancer patients when compared to standalone TACE. It appears to contribute to improved treatment outcomes, enhanced quality of life, and potentially reduced adverse reactions, suggesting it warrants further investigation as a promising approach for liver cancer treatment.